Pembuatan dan Pemasangan Instalasi Penerangan Bertenaga Surya Untuk Tempat Perahu Bersandar di Kampung Nelayan Kalisari - Syamsuri, Syamsuri; Maulana, Hasan Syafik; Saidatin, Naili; Rosidah, Afira Ainur; Setyowati, Vuri Ayu; Sasongko, Sukendro Broto; Noerpamoengkas, Ardi; Wardani, Iftika Philo; Lillahulhaq, Zain; Vietanti, Frizka (Institut Teknologi Adhi Tama Surabaya, 2024)
Residents who work as fishermen in Kalisari tether their boats by the river close to their settlements. To maintain the safety of the boat, residents need adequate lighting around the riverbanks. However, currently, the area used as a boat mooring area does not yet have sufficient lighting. Residents set up guard posts around the boat mooring area to maintain the boat's safety and gather when an association meeting is held. The boat mooring area is also an area for children to play on the riverbank. The installation of lighting is an essential requirement for the community to make monitoring the area around the mooring area easier. The installation of solar-powered lighting is carried out to solve this problem. In this activity, the service team also provided education on solar energy for Kalisari residents. Residents were also given training in the assembly and maintenance of installed solar panels. Service activities carried out in the fishing village of Kalisari received a positive response from the community. This can be seen from the enthusiasm of the community in attending the socialization activities. The installation of lamps equipped with solar panels received positive responses from residents, marked by the community's enthusiasm.